2014
DOI: 10.3389/fnins.2014.00217
|View full text |Cite
|
Sign up to set email alerts
|

Urinary oxytocin positively correlates with performance in facial visual search in unmarried males, without specific reaction to infant face

Abstract: The neuropeptide oxytocin plays a central role in prosocial and parental behavior in non-human mammals as well as humans. It has been suggested that oxytocin may affect visual processing of infant faces and emotional reaction to infants. Healthy male volunteers (N = 13) were tested for their ability to detect infant or adult faces among adult or infant faces (facial visual search task). Urine samples were collected from all participants before the study to measure the concentration of oxytocin. Urinary oxytoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Moreover, the relationships between peripheral and central measurements of OT have been debated,; albeit a study in mice has shown that peripheral administration can elevate both central and peripheral indices of OT . Importantly, recent studies have demonstrated associations between levels of urinary OT and attachment related behaviors such as gaze, maternal care giving, vocalization, and brain reaction to infants, further validating the use of this measure in the context of the mother–infant relationship. In addition, it has been found that intranasal OT administration can elevate levels of OT in urine, while simultaneously affecting brain reactivity .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationships between peripheral and central measurements of OT have been debated,; albeit a study in mice has shown that peripheral administration can elevate both central and peripheral indices of OT . Importantly, recent studies have demonstrated associations between levels of urinary OT and attachment related behaviors such as gaze, maternal care giving, vocalization, and brain reaction to infants, further validating the use of this measure in the context of the mother–infant relationship. In addition, it has been found that intranasal OT administration can elevate levels of OT in urine, while simultaneously affecting brain reactivity .…”
Section: Discussionmentioning
confidence: 99%
“…CSF, urine, and plasma samples are generally unsuitable in these situations as the collection method is invasive and painful; furthermore, it is unlikely that parents will provide consent for their infant’s participation in a study with these extraction methods. Finding correlations between oxytocin concentrations in urine and social behavior has shown some success in both animal and human studies ( 56 , 57 ). However, this collection method may still not be appropriate when attempting to determine an acute infant increase in oxytocin in response to a parent-infant interaction, as urine concentrations represent accumulated oxytocin concentrations and are not always readily available for collection, especially in infants.…”
Section: Considerations For Researchmentioning
confidence: 99%
“…If this is possible, we may then compare the results of marmoset studies with those in humans (e.g., Strathearn et al, 2008). It may then be possible to use marmosets to investigate the relationship between visual cognitive function and endocrinological factors that has been shown to be important in humans (Saito et al, 2014). Macaque monkeys are more closely related to humans than marmosets in evolutionary termis, and there are some key differences between new world monkeys (including marmosets and tamarins) and old world primates (including humans and macaque monkeys).…”
Section: Can Marmosets Be Used Model For Primate Parental Behavior?mentioning
confidence: 98%